Explaining health behavior: a new model centered around health experience and its determinants - Broekharst, Damien S. E.; Bloem, Sjaak; Groenland, Edward A. G.; Folkertsma, Tessa S.; Ingebretsen Carlson, Jim; Folkvord, Frans; Everitt, Claire; Liefveld, Aad R.; Fico, Giuseppe; Lupiáñez-Villanueva, Francisco (Frontiers in Psychology, 2025)
IntroductionConventional health-related models used to predict health behaviors have limited predictive power, as they fail to accurately capture an individual’s health experience, which correlates more closely with health behavior. Therefore, some researchers have aimed to develop a predictive model focused on subjective health experience and its determinants. Although this model may be promising, it is still rudimentary. Hence, this study aimed to explore a new extended subjective health experience model and segment it along the lines of relevant demographic variables to further improve health behavior predictions.MethodAn online questionnaire was administered to a panel of 2,550 Dutch citizens, covering sample characteristics and measuring health perceptions, acceptance, control, projected health, experienced health, adjustment, and health behavior. Data were analyzed using descriptive, reliability, validity, and model statistics.ResultThe analysis revealed that almost all assumed direct relationships within the overall and segmented models are statistically significant, making them exceptionally robust. It also became clear that health perception indirectly influences health behavior through several pathways. The strongest indirect pathways linking health perception to health behavior involve sequential mediation by acceptance, experienced health, and projected health, with control potentially preceding or replacing acceptance. The most moderate indirect pathways involve acceptance with either experienced or projected health, with control potentially preceding or replacing acceptance. The weaker indirect pathways are those involving adjustment either combined with experienced and projected health or embedded within more extended sequences. It further became evident that the model explained between 39.2 and 50.9% of the variance in health behavior.ConclusionHealthcare professionals and other stakeholders may benefit from using key concepts such as acceptance, control, experienced health, and projected health to guide the development and implementation of future behavioral interventions.